1977
DOI: 10.1007/bf00426579
|View full text |Cite
|
Sign up to set email alerts
|

Effects of withdrawal from chronic amphetamine intoxication on exploratory and stereotyped behaviors in the rat

Abstract: Rats were administered 3, 6, and 12 mg/kg of d-amphetamine s.c. twice daily on a weekly increasing staircase schedule. On days 1, 7, 14, and 28 after the last injection of amphetamine the animals were challenged with 1 and 3 mg/kg of d-amphetamine and their behavior was observed. The 7-, 14-, and 28-day withdrawn animals required less amphetamine than controls to induce stereotyped behaviors. However, it was found that withdrawn animals and control animals were equally sensitive to the effects of apomorphine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2

Year Published

1981
1981
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 14 publications
1
12
2
Order By: Relevance
“…The previous studies revealed the importance of a deprivation period in order to measure increases in reinforcing efficacy of cocaine following cocaine selfadministration. This finding by Morgan and colleagues is consistent with several reports indicating the importance of an "incubation" period in psychostimulant sensitization (Hitzemann et al 1977;Paulson et al 1991;Paulson and Robinson 1995;Vanderschuren et al 1997;Grimm et al 2001Grimm et al , 2003Di Ciano and Everitt 2002). In the present study, however, we report that no deprivation period is necessary to produce cross-sensitization by opioids to the reinforcing effects of cocaine.…”
Section: Discussionsupporting
confidence: 93%
“…The previous studies revealed the importance of a deprivation period in order to measure increases in reinforcing efficacy of cocaine following cocaine selfadministration. This finding by Morgan and colleagues is consistent with several reports indicating the importance of an "incubation" period in psychostimulant sensitization (Hitzemann et al 1977;Paulson et al 1991;Paulson and Robinson 1995;Vanderschuren et al 1997;Grimm et al 2001Grimm et al , 2003Di Ciano and Everitt 2002). In the present study, however, we report that no deprivation period is necessary to produce cross-sensitization by opioids to the reinforcing effects of cocaine.…”
Section: Discussionsupporting
confidence: 93%
“…In some studies, a period of drug abstinence enhanced the chronic drug response to indirect dopamine agonists (e.g., Hitzemann et al 1977;Post 1980;Kolta et al 1985;Robinson and Becker 1986;Antelman 1988;Paulson et al 1991;Paulson and Robinson 1995). However, in the present study drug abstinence did not enhance the sensitized locomotor response to QNP as evidenced by similar dose-response profiles 3 and 15 days post-chronic QNP treatment.…”
Section: Contribution Of Temporal Factors To Sensitizationcontrasting
confidence: 65%
“…>7 days), but not shorter (i.e. <7 days) periods of drug abstinence (Hitzemann et al 1977;Kolta et al 1985;Antelman and Caggiula 1991;Paulson et al 1991;Paulson and Robinson 1995;Szumlinski et al 1999aSzumlinski et al , 1999b.…”
Section: Introductionmentioning
confidence: 99%
“…The locomotor sensitization literature has consistently reported that a drug-free period enhances the degree of sensitization observed (Hitzemann et al 1977;Paulson et al 1991;Paulson and Robinson 1995). There is an emerging literature describing changes in extinction and/or reinstatement responding that vary as a function of withdrawal duration (Grimm et al 2001(Grimm et al , 2003Di Ciano and Everitt 2002).…”
mentioning
confidence: 97%